2002
DOI: 10.1063/1.1423394
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of laser-driven electron acceleration in vacuum

Abstract: The interaction of free electrons with intense laser beams in vacuum is studied using a 3D test particle simulation model that solves the relativistic Newton-Lorentz equations of motion in analytically specified laser fields. Recently, a group of solutions was found for very intense laser fields that show interesting and unusual characteristics. In particular, it was found that an electron can be captured within the high-intensity laser region, rather than expelled from it, and the captured electron can be acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(31 citation statements)
references
References 47 publications
1
30
0
Order By: Relevance
“…Many theoretical and experimental models were proposed and developed which target the sequential improvement in electron energy gains [1][2][3][4]. Wang et al [3] reported laser plasma acceleration to 2 GeV with pettawatt pulses.…”
Section: Introductionmentioning
confidence: 99%
“…Many theoretical and experimental models were proposed and developed which target the sequential improvement in electron energy gains [1][2][3][4]. Wang et al [3] reported laser plasma acceleration to 2 GeV with pettawatt pulses.…”
Section: Introductionmentioning
confidence: 99%
“…The other option is for the electron to spend a longer time period in the laser field. This is best achieved via a capture and acceleration scenario (CAS) [24][25][26] where the electron enters the field and gets captured near the focus and subsequently accelerated. For such a situation to occur we should have a high energy electron interacting with the laser pulse in a same direction (or near same direction) collision.…”
Section: The Set-upmentioning
confidence: 99%
“…During the interaction of an intense laser with plasma, a magnetic field is genera− ted and cyclotron resonance occurs between the electrons and the electric field of the laser beam and as a result the electrons are effectively accelerated to the high energies [28]. This type of resonance interaction was suggested as a mechanism for accelerating electrons to the relativistic energies [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…The ponderomotive deflection of electrons subjected to the electromagnetic field of an intense laser beam may significantly increase the electron energy. When laser intensity is very high, an electron can be captured within the high intensity laser region and can be accelerated to GeV and TeV energies [29,30]. In order to deflect already accelerated electrons from the laser beam, the external static magnetic field can be applied in the (x, y) plane perpendicu− lar to the beam axis.…”
Section: Introductionmentioning
confidence: 99%